(untitled) (Research, Society and Development, 2025)
This article aims to present the investigation and results of the effects of tempering heat treatments on austenitic manganese steel, with the aim of improving its mechanical properties, particularly hardness and toughness, providing longer service life and a reduction in operating costs. However, manganese steel is widely used in high abrasion environments due to its excellent wear resistance, but its properties can be optimized through appropriate heat treatments. To achieve this objective, the manganese steel specimens were subjected to a quenching process at 1100°C with a residence time inside the furnace of up to 1 hour. However, the cooling media used in the process were water and oil. The results showed a significant increase in hardness after quenching with water cooling, and a reduction in oil quenching. The conclusions of this investigation indicate that water quenching is an effective heat treatment to improve the hardness of Hadfield steel, increasing the service life of the material.